The prevention of infection in open fractures: an experimental study of the effects of fracture stability and of antibiotic therapy - Worlock, Peter Harrison (1986)
An experimental model of a contaminated open fracture has been developed in rabbits, using a reproducible midshaft fracture of the tibia. This model has been used to: